(untitled) (Academic Journal of Internal Affairs, 2020)
The author intends to get answers to the questions: what successful law enforcement leadership means, what kind of leaders can be successful, what is the background of their success. In this paper he summarises leaders’ attitudes, theories, models and leaders’ competencies.